Apakah Pendidikan Tinggi Meningkatkan Kemungkinan untuk Bekerja di Sektor Formal? - Maulana, Rizky (Jurnal Ekonomi Kuantitatif Terapan; 2020: Vol. 13, No. 1, Februari 2020 (pp. 1-210), 2020)
This research aims to see whether tertiary education graduates are more likely to be employed in a formal sector than lower levels of education. Formal employment has a much higher wage rate than the informal sector. Students who go on to higher education have high expectations for their standard of living in the future, but there are still college graduates who work in the informal sector. To answer the purpose of this research, the writer uses probit regression. From these regressions, significant results were obtained. Higher education increases one's chances of being employed in the formal sector. Likewise, the sex and age variables. Male workers have a higher chance of being employed while the older labor forces have smaller chances of being employed in a formal sector.